Vertwillium Wilt of Polyalthia longifolia - a New Disease Report from India - Kumar, Rajesh; Baruah, Debu Moni; Tapwal, Ashwani; Borah, R. K. (Indian Forester, 2010)
Verticillium dahliae was identified as a pathogen causing wilt disease of Polyalthia longifolia. It was isolated from the infected roots of the seedlings collected from Central Forest Nursery of Imphal, Manipur, India. Four fungicides viz. Bavistin 50% WP, Dithane M-45, Dithane Z-78 and Fytolan 50% WP were screened against the pathogen at different concentrations using poison food technique in vitro and then in field-conditions using soil drenching technique. The results revealed that Bavistin 50% WP was most effective at 75 ppm with 100% growth inhibition followed by Dithane M-45, Dithane Z-78 and minimum efficacy was observed by Fytolan 50% WP with 31.27% growth inhibition in laboratory conditions. All selected fungicides were evaluated against pathogen in field conditions at 0.1% and 0.2 % concentrations. Bavistin 50% WP was found to be the most effective at 0.2% concentration. Thus the present study recommends soil drenching with Bavistin 50% WP at aminimal concentration of 0.2% for management of the disease.